2021
DOI: 10.7554/elife.66519
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 deletion in brown adipose tissue improves thermoregulation and systemic metabolism via FGF21

Abstract: Adrenergic stimulation of brown adipocytes alters mitochondrial dynamics, including the mitochondrial fusion protein optic atrophy 1 (OPA1). However, direct mechanisms linking OPA1 to brown adipose tissue (BAT) physiology are incompletely understood. We utilized a mouse model of selective OPA1 deletion in BAT (OPA1 BAT KO) to investigate the role of OPA1 in thermogenesis. OPA1 is required for cold-induced activation of thermogenic genes in BAT. Unexpectedly, OPA1 deficiency induced fibroblast growth factor 21 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
75
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 51 publications
12
75
2
Order By: Relevance
“…Other studies have showed that non-thermogenic modalities of increasing BAT activity and mass, through methods like BAT transplantation [12], also lead to an increase serum FGF21. These findings along with other recent studies could suggest that the secretion of BATderived FGF21 and its subsequent metabolic effects may not be specifically linked to BAT thermogenic activity [36].…”
Section: Bat-and-liver Crosstalk: Regulation Of Whole-body Metabolismsupporting
confidence: 55%
“…Other studies have showed that non-thermogenic modalities of increasing BAT activity and mass, through methods like BAT transplantation [12], also lead to an increase serum FGF21. These findings along with other recent studies could suggest that the secretion of BATderived FGF21 and its subsequent metabolic effects may not be specifically linked to BAT thermogenic activity [36].…”
Section: Bat-and-liver Crosstalk: Regulation Of Whole-body Metabolismsupporting
confidence: 55%
“…Branched chain amino acids (BCAA), including leucine, isoleucine, and valine, play a crucial role in the activation of the TOR pathway [71]. Mitochondrial stress can be regulated by Tor through activation of ATF4 to induce the integrated stress response and activation of GCN2 to increase amino acid availability [72][73][74][75][76][77][78][79][80], which we believe to be a protective response. We hypothesize that the lower BCAA levels in the A population (Figure 2D(i)) indicate that they are not able to effectively activate this pathway.…”
Section: Metabolomic Characterizationmentioning
confidence: 92%
“…Elevated levels of FGF21 (both circulation and mRNA) have been observed in cases of several metabolic disorders (NAFLD, obesity, T2DM), which suggests protective activities against those diseases [208]. In addition, FGF21 could be secreted from the brown adipose tissue and participate in thermoregulation in an ATF4-dependent way [209]. Several FGF21 analogues have been clinically tested as promising NAFLD treatments.…”
Section: Pharmaceutical Strategies To Treat Nafld and Reduce Cvd Riskmentioning
confidence: 99%